PERBEDAAN FARDHU DAN WÂJIB MENURUT MAZHAB FIQH - Shohibul Wafa Tadzul Arifin; Mustofa Mustofa (AL-SYAKHSHIYYAH Jurnal Hukum Keluarga Islam dan Kemanusiaan, 2023)
This article discusses the differences between the concepts of Fardhu and  wâjib in ahkamul khamsah, by analyzing the opinions of madhhab scholars. This study uses a normative method with a literature review sourced from the books of fiqh scholars. The results of the analysis show that the majority of fuqaha equate wâjib and fardhu at the term and application level even though they differ in naming. However, the madhhab Hanafi believes that there is a special term in the case of worship which makes wâjib and fardhu different.